PENERAPAN SISTEM PELAPORAN KEUANGAN DIGITAL BERBASIS WEB PADA SEKOLAH SMU DAN SMP SWASTA SEKITAR KAMPUS UTM JAKARTA (Jurnal Akuntansi, 2023)
This research aims to find out school financial reports that comply with the financial reporting guidelines set by the authorities quickly and precisely, without space and time constraints and can be done 24 hours and anywhere. As well as getting a financial accounting information system that is always up to date. The analytical method used is through a quantitative observation approach in the form of observations and interviews with research objects (partners) and direct data collection in the field. This research is a derivative of the tridharma activities of higher education, namely Community Service (PKM) activities. The results of this research show that the average knowledge of respondents before and after participating in the training shows that there is a significant difference in knowledge and understanding.Keywords: Digital Financial Reporting, Web Based, SMP, SMU